2003
DOI: 10.1093/brain/awg222
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory and autonoetic consciousness: triple dissociation in neurodegenerative diseases

Abstract: Few studies have investigated autobiographical amnesia in neurodegenerative diseases and yet these pathologies are particularly relevant when addressing the issue of theories of long-term memory consolidation. According to the standard model, the medial temporal lobe (MTL) is involved in the storage and retrieval of episodic and semantic memories during a limited period of years. An alternative model, the multiple trace theory (MTT), suggests that the capacity of the MTL to recollect episodic memories is of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
270
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(296 citation statements)
references
References 112 publications
23
270
0
3
Order By: Relevance
“…While episodic memory deficits could be partly due to semantic memory impairments, the use of a visual episodic task in our study suggests genuine episodic memory impairment, although definitely less serious than in Alzheimer Disease patients [52,58]. Finally, all the patients who underwent the behavioural assessment presented various changes, in line with growing evidence that many patients with SD have behavioural changes, sometimes identical to those suffering from the frontal variant of frontotemporal dementia [5,18,39,54,65,67].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While episodic memory deficits could be partly due to semantic memory impairments, the use of a visual episodic task in our study suggests genuine episodic memory impairment, although definitely less serious than in Alzheimer Disease patients [52,58]. Finally, all the patients who underwent the behavioural assessment presented various changes, in line with growing evidence that many patients with SD have behavioural changes, sometimes identical to those suffering from the frontal variant of frontotemporal dementia [5,18,39,54,65,67].…”
Section: Discussionsupporting
confidence: 83%
“…Left-sided predominant atrophy is more frequent than right predominant or symmetrical involvement (e.g., [7,26,29]). Visual inspection of MRI brain scans has suggested that the hippocampal complex is preserved in SD, which might fit with normal day-to-day memory, or near normal performance on episodic memory tests in some patients [27,28,57,58]. Some authors [29,9] did not find significant atrophy of the hippocampus and adjacent structures using the SPM software which allows a voxel-by-voxel analysis (Voxel Based Morphometry, VBM) of the entire brain.…”
Section: Introductionmentioning
confidence: 99%
“…These results may reflect two sides of sense of identity, one being relatively general and quite stable, and therefore preserved even in the presence of extensive cognitive and neural damage, the other varying over time and with experience, and therefore more fragile, especially in the case of severe impairment of both episodic and semantic retrograde memory (Haslam et al, 2011;Piolino et al, 2003).…”
Section: Conclusion and Phenomenological Considerationsmentioning
confidence: 99%
“…When memories of past experiences are impaired, as they are in AD, the sense of existing in the past must be dramatically compromised. Given the temporal gradient of memory impairment in AD (Piolino et al, 2003), patients may travel back to the time in their lives for which they have the clearest memories, the resulting gap being resolved by their continuity of sense of identity. The selfrepresentation of age, a component of sense of identity, is thus dependent upon subjective time and becomes tied to the best preserved episodic memories.…”
mentioning
confidence: 99%
“…More concretely, participants are asked to report whether they recognise items through recollection of episodic 3 details of the encoding context (Remember) or through a feeling of familiarity without any recollective experience (Know). Most of the studies that assessed the subjective aspects of recollection and familiarity in AD patients by using the Remember-Know procedure found that the experience of remembering, but not familiarity, was significantly impaired in AD patients (Dalla Barba, 1997;Piolino et al, 2003;Rauchs et al, 2007). However, a more recent study has found that both Remember and Know responses were reduced in AD patients (Hudon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%